2023
DOI: 10.1097/bsd.0000000000001517
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Disability Influences Effectiveness of MCID and PASS in Predicting Patient Improvement Following Lumbar Spine Surgery

Pratyush Shahi,
Tejas Subramanian,
Omri Maayan
et al.

Abstract: Study Design: Retrospective cohort. Summary of Background Data: Although minimal clinically important difference (MCID) and patient acceptable symptom state (PASS) are utilized to interpret Oswestry Disability Index (ODI), it is unclear whether there is a clearly better metric between the two and if not, which metric should be utilized when. Objective: To compare the characteristics of MCID and PASS when int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Especially among patients undergoing revision spine surgery, the benefits of surgery are significant even if the absolute symptom state is not considered acceptable in some patient populations [34,35]. Recently, Shahi et al suggested postoperative improvement is best assessed by PASS in patients with minimal or moderate preoperative disability while MCID is an optimal metric for patients with severe preoperative disability [36]. In their population of 212 primary minimally invasive spine fusion patients, 19% achieved PASS but not MCID and 10% of achieved MCID but not PASS, with primary difference being a poorer preoperative ODI in the second group.…”
Section: Discussionmentioning
confidence: 99%
“…Especially among patients undergoing revision spine surgery, the benefits of surgery are significant even if the absolute symptom state is not considered acceptable in some patient populations [34,35]. Recently, Shahi et al suggested postoperative improvement is best assessed by PASS in patients with minimal or moderate preoperative disability while MCID is an optimal metric for patients with severe preoperative disability [36]. In their population of 212 primary minimally invasive spine fusion patients, 19% achieved PASS but not MCID and 10% of achieved MCID but not PASS, with primary difference being a poorer preoperative ODI in the second group.…”
Section: Discussionmentioning
confidence: 99%